PLATO and Ariel, the next medium-class Missions of the ESA’s roadmap on the discovery and characterization of exoplanets from space: the contribution of INAF-OAA - Focardi, Mauro (Il Colle di Galileo, 2022)
Since some years, the Arcetri Astrophysical Observatory plays a crucial role in the contribution to the European Space Agency (ESA) roadmap on exoplanets discovery and characterization from space (ref. Figure 1). Several of its Researchers, Technologists and Technician, thanks also to the local Administrative Department support, are involved in the PLATO and Ariel Payloads design and development, along with the scientific aspects aimed at the study of exoplanets.